Trading N and O. Part 2: Exploiting aziridinium intermediates for the synthesis of β-hydroxy-α-amino acids - Davies, S; Fletcher, A; Frost, AB; Roberts, P; Thomson, J (Elsevier, 2014)
The β-hydroxy-α-amino acids (S,S)-allo-threonine, (S,S)-β-hydroxyleucine and a range of aryl substituted (S,S)-β-hydroxyphenylalanines were prepared from the corresponding enantiopure anti-α-hydroxy-β-amino esters via a rearrangement protocol, which proceeds via the intermediacy of the corresponding aziridinium ions. The starting anti-α-hydroxy-β-amino esters were prepared in >99:1 dr using our diastereoselective aminohydroxylation procedure, whereby conjugate addition of lithium (R)-N-benzyl-N-(α-methylbenzyl)amide to an α,β-unsaturated ester is followed by oxidation of the resultant enolate with (-)-camphorsulfonyloxaziridine. Subsequent activation of the hydroxyl group within the anti-α-hydroxy-β-amino esters promoted aziridinium ion formation [which proceeds with inversion of configuration at C(2)], and regioselective ring-opening of the intermediate aziridinium ions with H2O [which proceeds with inversion of configuration at C(3)] gave the corresponding anti-β-hydroxy-α-amino esters as single diastereoisomers (>99:1 dr). Deprotection of these substrates via sequential hydrogenolysis and ester hydrolysis gave the corresponding β-hydroxy-α-amino acids in good yield and high diastereoisomeric and enantiomeric purity.